Aluminum pigment, method for producing aluminum pigment, coating composition and ink composition containing aluminum pigment
Patent Information
- Application Number
- JP2023546936
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2022-03-04
- Filing Date
- 2022-09-05
- Publication Date
- 2025-03-06
- Estimated Expiration
- 2042-09-05
AI Technical Summary
【0011】 本発明によれば、高い緻密感が得られ、正反射に近いハイライト領域での高い輝度と、広い反射領域においても高い明度を示すメタリック意匠に加え、良好な分散·作業性や高い光沢度を実現可能なアルミニウム顔料(組成物)を提供することができる。
Smart Images

Figure 0007641394000003 
Figure 0007641394000004 
Figure 0007641394000005
Abstract
Description
[Technical field]
[0001] The present invention relates to an aluminum pigment and a method for producing the same, and a coating composition and an ink composition each containing the aluminum pigment. [Background technology]
[0002] Aluminum pigments have been widely used in various fields as pigments that combine a unique metallic look not found in other pigments with excellent hiding power for the base. In recent years, in the painting of automobile bodies, painting of automobile interior parts, metallic painting for optical equipment, etc., importance has been placed on a more detailed, high brightness, brilliance, and glossy appearance that gives off a luxurious feel. It is expected that these will become even more important in the future from the perspective of demonstrating value equal to or greater than the original functionality of the product.
[0003] One method for achieving the above-mentioned excellent appearance characteristics is to reduce the size of aluminum pigment particles, which is known to be effective in improving the sense of density. However, when the aluminum pigment particles are made finer, the orientation of the particles in the coating film decreases, causing problems such as a decrease in brightness and an increase in the occurrence of scattered light. On the other hand, when the diameter of the aluminum pigment particles is increased, there is a problem that the particles become conspicuous in the coating film as a glaring graininess.
[0004] One method to solve this problem is to thin the aluminum particles. For example, Patent Document 1 discloses an aluminum pigment that can achieve a plated appearance with excellent metallic luster by increasing the grinding time of raw aluminum powder to form thin aluminum particles. Furthermore, Patent Documents 2 and 3 disclose specific thin-film aluminum pigments, and aim to improve workability, such as dispersibility, by specifying the thickness distribution (range of relative width Δh) and aspect ratio of the aluminum particles. Furthermore, Patent Document 4 discloses a method for producing an aluminum pigment by a metal vapor deposition method. This production method employs a method that is completely different from the method for producing an aluminum pigment by mechanical processing using a pulverizer, and produces aluminum particles with a thin, uniform film thickness and excellent smoothness, making it possible to obtain a dense appearance, high brightness, and high gloss. Furthermore, Patent Document 5 proposes a method for realizing a strong metallic feel by reducing the amount of fine particle components and specifying the number of particles with a particle size of 1 μm or less in the entire aluminum pigment. Moreover, Patent Document 6 proposes a method for realizing a mirror-like metallic design by increasing the planarity of particles. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2003-82258 A [Patent Document 2] JP 2014-159583 A [Patent Document 3] International Publication No. 2004 / 087816 Brochure [Patent Document 4] Special Publication No. 2002-528639 [Patent Document 5] International Publication No. 2019 / 077904 Brochure [Patent Document 6] International Publication No. 2017 / 030077 Brochure Summary of the Invention [Problem to be solved by the invention]
[0006] Looking at the design trends in automotive body coatings, automotive interior part coatings, and metallic coatings for optical equipment, in addition to the traditionally high demand for high brightness and high gloss metallic designs, there is an increasing demand for metallic designs with a sense of detail and extremely high brightness in the highlight area close to regular reflection. However, in designs that use many futuristic curved shapes and curved surfaces, there is a problem that the optical anisotropy characteristic of aluminum pigments results in many dark areas depending on the viewing angle, preventing the brightness, gloss, and sense of detail from being fully realized. Therefore, there is an increasing demand for metallic designs that maintain high brightness in the highlight area close to regular reflection while also having high brightness in a wide reflection area, i.e., there is little color change depending on the viewing angle and little angle dependency. Furthermore, in recent years, as design has become more sophisticated, aluminum pigments have become finer and thinner, which means that their dispersibility when made into paints tends to deteriorate. This not only deteriorates design, but also leads to worsening workability, so there is an increasing demand for easy dispersibility. Also, in the field of high-end printing inks such as gravure printing, offset printing, and screen printing, there is an increasing demand for equivalent metallic designs and easy dispersibility.
[0007] However, the aluminum pigments described in the above-mentioned Patent Documents 1 to 3 obtain excellent metallic luster by thinly stretching aluminum particles, but have the problem that they do not yet provide sufficient characteristics in terms of achieving high density, high brightness in the highlight region, high brightness in a wide reflection region, and even easy dispersibility and high luster. In addition, the aluminum pigment described in Patent Document 4 also has high density and high brightness because it is produced by a vapor deposition method. However, dispersibility tends to be poor due to the influence of the release agent used in the production process, and so, similarly to the above, there is a problem in that sufficient characteristics have not yet been obtained in terms of achieving high density, high brightness in the highlight region, high brightness in a wide reflection region, and even easy dispersibility and high gloss. Furthermore, in the aluminum pigment described in Patent Document 5, the brightness is increased by reducing the amount of fine particle components and specifying the number of particles with a particle size of 1 μm or less in the entire aluminum pigment, but the granular feel of the aluminum is not taken into consideration, and there is a problem in that sufficient characteristics have not yet been obtained in terms of realizing a high sense of density, high brightness in the highlight region, high brightness in a wide reflection region, and even high gloss. In addition, the aluminum pigment described in Patent Document 6 can also realize a mirror-like metallic design by improving the flatness of the particles, but has the problem that sufficient characteristics are not yet obtained in terms of high density and high gloss. As described above, all of the techniques proposed to date have a problem in that they have not provided an aluminum pigment that can achieve all of the following: high density, high luminance in the highlight region, high lightness in a wide reflection region, and also easy dispersibility and high gloss.
[0008] In view of the above-mentioned problems with the conventional techniques, the present invention aims to provide an aluminum pigment (composition) that is capable of realizing a metallic design and that is excellent in optical properties, dispersibility, and workability, and that satisfies all of the requirements of high density, high luminance in the highlight region, high brightness in a wide reflection region, and furthermore, easy dispersibility and high gloss. [Means for solving the problem]
[0009] As a result of extensive investigation into the problems of the prior art described above, the inventors focused on the cross-sectional shape of metallic aluminum particles in an aluminum pigment and the fine particle content, and discovered that by setting the thickness and aspect ratio of metallic aluminum particles in the cross section of a coating film within specific ranges, as well as limiting the amount of fine particles contained in the aluminum pigment and the planarity of the particles, it is possible to obtain an aluminum pigment that has a high sense of density, maintains high luminance in a highlight region close to regular reflection, while also exhibiting high lightness in a wide reflection region, in other words, has little color change depending on the viewing angle, is capable of expressing a metallic design with little angle dependency, and is also excellent in dispersibility, workability and gloss, and has thus completed the present invention. That is, the present invention is as follows.
[0010] [1] The average thickness of the metallic aluminum particles is 0.02 to 0.20 μm, and the average aspect ratio (particle cross-sectional length / particle cross-sectional thickness) is 40 to 90 And the standard deviation of the aspect ratio is 15~ 47.1 Yes The ratio of the number of particles having an aspect ratio of 110 or more to the total number of particles is 30% or less. Aluminum pigment. [2] The aluminum pigment according to [1], wherein the proportion of the number of particles having an aspect ratio of 20 or less is 30% or less of the total number of particles. [3] The particles have an arithmetic mean height Sa of surface roughness of 2 to 15 nm. [1] or [2] The aluminum pigment according to the present invention. [4] The aluminum pigment according to any one of [1] to [3], wherein the particles have an average thickness of 0.03 to 0.15 μm. [5] The aluminum pigment according to any one of [1] to [4], wherein the particles have an average aspect ratio of 40 to 90. [6] The aluminum pigment according to any one of [1] to [5], comprising metallic aluminum particles in which the number ratio of particles having a particle diameter of 0.2 to 2.0 μm is 15 to 70% of the total number of metallic aluminum particles. [7] The aluminum pigment according to any one of [1] to [6], wherein the particles contain planar particles having a planarity (shortest length / particle cross-sectional length) of 0.95 to 1.00 in a number ratio of 60% or more. [8] [1] to [7], a method for producing an aluminum pigment according to any one of the above, comprising the steps of grinding a raw material aluminum metal powder using a grinding device, and classifying a slurry obtained after grinding. [9] The method for producing an aluminum pigment according to [8], wherein the grinding step is carried out in two stages.
[10] A coating composition comprising the aluminum pigment according to any one of [1] to [7].
[11] An ink composition comprising the aluminum pigment according to any one of [1] to [7]. Effect of the Invention
[0011] According to the present invention, it is possible to provide an aluminum pigment (composition) which can achieve a metallic design that has a high sense of density, high luminance in the highlight region close to regular reflection, and high brightness even in a wide reflection region, as well as good dispersibility, workability, and high gloss. [Brief description of the drawings]
[0012] [Figure 1] Fig. 1 shows an example of a photograph of an FE-SEM image of the cross section of an aluminum pigment particle obtained using a field emission FE-SEM (Hitachi / S-4700) to explain a method for evaluating the particle cross-sectional thickness and aspect ratio of metallic aluminum particles in an aluminum pigment. The white, horizontally elongated objects in the photograph correspond to metallic aluminum particles. In Fig. 1, the white parts correspond to the cross-sectional area of the metallic aluminum particle, the left-right direction corresponds to the particle cross-sectional length, and the up-down direction corresponds to the particle cross-sectional thickness. [Diagram 2]Fig. 2 shows an example of a photograph of an observation image of the particle surface of an aluminum pigment obtained using a microscope (Hirox / KH-3000) to explain a method for evaluating the proportion of the number of metallic aluminum particles with particle diameters of 0.2 to 2.0 μm in an aluminum pigment. The white circular and irregularly shaped objects of various sizes in the photograph correspond to metallic aluminum particles. In Fig. 2, the white parts mainly correspond to the particle shapes observed from a plane perpendicular to the thickness direction of the metallic aluminum particles. [Diagram 3] shows an example of a photograph of an FE-SEM image of the cross section of an aluminum pigment particle obtained using a field emission type FE-SEM (Hitachi / S-4700) to explain a method for evaluating the planarity of aluminum pigment particles. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] Hereinafter, an embodiment of the present invention (hereinafter, referred to as "the present embodiment") will be described in detail. The following embodiments are merely illustrative for explaining the present invention, and are not intended to limit the present invention to the following contents. The present invention can be modified appropriately within the scope of the gist thereof.
[0014] [Aluminum pigment] The aluminum pigment of this embodiment has an average thickness t of metal aluminum particles determined by cross-sectional observation of 0.02 to 0.20 μm, an average aspect ratio (particle cross-sectional length / particle cross-sectional thickness) of 40 to 100, and a standard deviation of the aspect ratio of 15 to 70. The metallic aluminum particles contained in the aluminum pigment of the present invention are preferably thin-film, scale-like or flake-like, have a small thickness and a flat shape, the particle diameter is a measurement value in a plane perpendicular to the thickness direction, and the average thickness and average aspect ratio (particle cross-sectional length / particle cross-sectional thickness) are measurements on the particle cross section.
[0015] In the aluminum pigment of this embodiment, the average thickness of the metallic aluminum particles, the aspect ratio (particle cross-sectional length / particle cross-sectional thickness), the percentage (%) of particles with a particle diameter of 0.2 to 2.0 μm, the arithmetic mean height Sa (nm) of the surface roughness, and the percentage (%) of planar particles are defined as follows.
[0016] The average thickness t and aspect ratio (particle cross-sectional length / particle cross-sectional thickness) of the metallic aluminum particles can be determined by obtaining an FE-SEM image of the cross section of a coating film formed with a coating composition containing the aluminum pigment of this embodiment and measuring the image using image analysis software. In the FE-SEM image of the cross section of the coating film, the contours of the metallic aluminum particles are extracted along their shapes using image analysis software, and the area and the length in the major axis direction are measured. The area / length of the extracted particle cross section is calculated, and the calculated value is taken as the "particle cross-sectional thickness." The ratio of the particle cross-sectional length to the particle cross-sectional thickness (particle cross-sectional length / particle cross-sectional thickness) is calculated, and the calculated value is defined as the "aspect ratio" of the particle. According to the above definition, the aspect ratios of 100 or more particles are calculated, and the average value and standard deviation are calculated. Similarly, from the image analysis results, the proportion of the number of particles with an aspect ratio of 20 or less to the total number of particles and the proportion of the number of particles with an aspect ratio of 110 or more to the total number of particles can be calculated. Preparation of the coating cross section, acquisition of the FE-SEM image, and image analysis can be carried out by the methods described in the Examples below.
[0017] The aluminum pigment of this embodiment has an average thickness of metallic aluminum particles determined from the above-mentioned cross-sectional observation of 0.02 to 0.20 μm, an average aspect ratio (particle cross-sectional length / particle cross-sectional thickness) of 40 to 100, and a standard deviation of the aspect ratio of 15 to 70, thereby enabling the brightness and luminance to be improved while maintaining a dense appearance, and a preferred design to be obtained. The cross-sectional thickness t (μm) of the metallic aluminum particles can be determined by measuring using an FE-SEM image of the coating cross section used in the measurement of the particle aspect ratio described above, and using image analysis software. Specifically, in an FE-SEM image of the cross section of the coating, image analysis software is used to extract the outline of the particle along with its shape, and the area / size (length) of the extracted particle cross section is calculated, and the calculated value is the "particle cross-sectional thickness." The average thickness t (μm) of the metallic aluminum particles can be obtained by calculating the arithmetic mean value of the thicknesses of 100 or more randomly selected particles. The average thickness t (μm) of the metallic aluminum particles in the aluminum pigment of this embodiment is 0.02 μm to 0.20 μm. By making the average thickness t 0.02μm or more, deformation and cracks of the particles can be suppressed and the surface smoothness can be maintained, resulting in high brightness. In addition, the dispersibility and workability when made into paint are good. By making the average particle thickness t 0.20 μm or less, the shadow area of the particle ends can be suitably adjusted, and a dense feel and high gloss can be obtained. The average thickness t (μm) of the metallic aluminum particles in the aluminum pigment of this embodiment is preferably 0.03 μm or more and 0.18 μm or less, more preferably 0.03 μm or more and 0.15 μm or less, even more preferably 0.04 μm or more and 0.16 μm or less, 0.04 μm or more and 0.14 μm or less, and even more preferably 0.05 μm or more and 0.13 μm or less. The average aspect ratio of the metallic aluminum particles in the aluminum pigment of this embodiment is 40-100. By having an average aspect ratio of 40 or more, high brightness, high lightness over a wide area, and higher hiding power can be obtained, and when used in painting, a dense and smooth coating film can be obtained. By making the average aspect ratio 100 or less, warping, distortion, and cracks in the particles can be suppressed. The average aspect ratio of the metallic aluminum particles in the aluminum pigment of this embodiment is preferably 40-90 or 45-95, more preferably 45-85, even more preferably 50-90, and even more preferably 50-80. Moreover, the standard deviation of the aspect ratio is 15 to 70. By having the standard deviation of the aspect ratio be 15 or more, high brightness can be maintained over a wide reflection area, and the difference in brightness depending on the angle can be suppressed. By having the standard deviation be 70 or less, high brightness and high gloss can be maintained in the regular reflection area. The standard deviation of the aspect ratio of the aluminum pigment of this embodiment is preferably 20-65.
[0018] In the aluminum pigment of this embodiment, the proportion of particles having an aspect ratio of 20 or less in number to the whole particles is preferably 30% or less. By making the proportion of particles having an aspect ratio of 20 or less 30% or less of the total number of particles, it is possible to obtain a metallic coating film having higher brightness and a metallic feel, which is preferable. In the aluminum pigment of this embodiment, the proportion of particles having an aspect ratio of 20 or less in number relative to the total is more preferably 20% or less.
[0019] In the aluminum pigment of this embodiment, the proportion of metal aluminum particles having an aspect ratio of 110 or more is preferably 30% or less based on the total number of particles. By making the proportion of particles having an aspect ratio of 110 or more 30% or less of the total number of particles, it is possible to suppress warping, distortion, and cracking of the particles, which is preferable. It is also preferable because it improves dispersibility and workability when made into a paint. In the aluminum pigment of this embodiment, the proportion of particles having an aspect ratio of 110 or more is more preferably 20% or less based on the total number of particles.
[0020] The arithmetic mean height Sa of the surface roughness (irregularities on the particle surface) of the metallic aluminum particles in the aluminum pigment of this embodiment is an index showing the smoothness of the surface of the aluminum pigment particles, and can be measured using an SPM (Scanning Probe Microscope), which includes an atomic force microscope, etc. The arithmetic mean height Sa is preferably 2 to 15 nm. When the arithmetic mean height Sa is 15 nm or less, the particle surface has high smoothness, so that the amount of specularly reflected light is increased, and a higher sense of brilliance is obtained. When the arithmetic mean height Sa is 2 nm or more, the grinding time required for producing the aluminum pigment of this embodiment is not extremely long, and the productivity is excellent. The arithmetic mean height Sa is more preferably from 2 to 12 nm.
[0021] The planarity (shortest length / particle cross-sectional length) of the metallic aluminum particles in the aluminum pigment of this embodiment can be determined by obtaining an FE-SEM image of the cross section of the coating film described above and measuring it using image analysis software. The measurement method will be explained. In the FE-SEM image of the cross section of the coating film, the measurement value of a straight line connecting both ends of the cross section of the particle is taken as the "shortest length." Also, the measurement value of a line connecting both ends of the cross section of the particle along the shape of the cross section of the particle is taken as the "cross-sectional length of the particle." The ratio of the shortest length to the particle cross-sectional length (shortest length / particle cross-sectional length) is defined as the planarity of the particle. The closer the particle flatness is to 1.00, the smaller the warping and distortion of the particle is. The planarity of 100 particles is determined according to the above definition. Regarding the degree of particle planarity, a threshold value for distinction is set to 0.95, particles in the range of 0.95 to 1.00 are defined as planar particles, and the ratio is calculated as the planar particle ratio (%) (%: number ratio). It is preferable that the content ratio of particles having a flatness in the range of 0.95 to 1.00 is 60% or more, since this makes it possible to maintain high brightness in the regular reflection region, and more preferably, 60% or more and 98% or less.
[0022] In the aluminum pigment of this embodiment, in order to realize a better gloss, it is preferable to use a specific ratio of metallic aluminum particles having a particle diameter of 0.2 to 2.0 μm. Increasing the diameter of the aluminum pigment particles is effective in improving metallic gloss. On the other hand, if the aluminum pigment particles are excessively large, the graininess in the coating film becomes noticeable, so it is preferable to control the number ratio of particles having a specific particle diameter within a certain range. Specifically, the proportion of the number of metallic aluminum particles having a particle diameter of 0.2 to 2.0 μm in the aluminum pigment of this embodiment is preferably 15 to 70% of the total number of particles determined from a photograph of an observation image of the particle surface of the aluminum pigment obtained using a microscope. By having the proportion of particles having a particle diameter of 0.2 to 2.0 μm, it is possible to achieve a high gloss while suppressing the graininess. The proportion by number of metallic aluminum particles having a particle diameter of 0.2 to 2.0 μm in the aluminum pigment of this embodiment is more preferably 20 to 65%. The proportion of metallic aluminum particles having a particle diameter of 0.2 to 2.0 μm can be adjusted to fall within the above-mentioned preferred range by carrying out the process of grinding raw metallic aluminum powder in two stages in the production method of an aluminum pigment described below, which has the effect of providing an aluminum pigment with a high gloss.
[0023] [Method of producing aluminum pigment] The method for producing the aluminum pigment according to the present embodiment will be described below. The method for producing an aluminum pigment according to the present embodiment includes a step of grinding raw aluminum metal powder (atomized aluminum powder) using a grinding device equipped with a ball mill or the like, and a step of classifying the slurry after grinding. The grinding step preferably includes a first step of smoothing the aluminum particles into a uniform thin film, and a second grinding step of adjusting the amount of fine particles of the aluminum particles according to the purpose (i.e., the grinding step is performed in two steps). By appropriately adjusting and combining conditions such as the particle size of the atomized aluminum powder used as the raw material, the mass per grinding ball used, the rotation speed of the grinding device, the grinding solvent, and the grinding aid, it is possible to adjust the average thickness of the above-mentioned particles, the aspect ratio (particle cross-sectional length / particle cross-sectional thickness), and the proportion of particles with particle diameters of 0.2 to 2.0 μm.
[0024] <Grinding process> When considering that the average particle thickness should be in the range of 0.02 to 0.20 μm, particularly preferred grinding conditions are as follows: the raw material is atomized aluminum powder, preferably having a particle size of 1.0 to 6.0 μm, more preferably 1.5 to 5.0 μm; the mass per ball of the grinding ball used in the grinding apparatus is preferably 0.08 to 11.00 mg, more preferably 0.08 to 9.00 mg; and the rotation speed of the grinding apparatus is 33% to 78% of the critical rotation speed (Nc), more preferably 36% to 57%.
[0025] <Grinding ball> The specific gravity of the grinding balls used in a ball mill or the like is preferably 8 or less, more preferably 7.5 or less, and even more preferably 7 or less, from the viewpoint of making it easier to adjust the particles and increasing the surface smoothness of the aluminum particles. The specific gravity of the grinding balls is preferably greater than that of the grinding solvent. By making the specific gravity of the grinding balls greater than that of the grinding solvent, the grinding balls can be prevented from floating in the solvent, and sufficient shear stress between the grinding balls can be obtained, which tends to allow grinding to proceed sufficiently.
[0026] As the grinding balls used in the method for producing an aluminum pigment of this embodiment, those with high surface smoothness, such as stainless steel balls, zirconia balls, and glass balls, are preferred from the viewpoints of adjusting the surface smoothness of the aluminum particles and the durability of the grinding balls. On the other hand, steel balls, alumina balls, etc., which have low surface smoothness, are not preferred from the viewpoints of adjusting the surface smoothness of the aluminum particles and the durability of the grinding balls. For this reason, for example, in the case of stainless steel balls, it is preferable to use balls whose surface smoothness has been increased by mechanical polishing and chemical polishing.
[0027] As described above, the mass of each grinding ball is preferably 0.08 to 11.00 mg. By using grinding balls with a mass of 0.08 mg or more per ball, it is possible to prevent the occurrence of so-called group motion, a phenomenon in which the grinding balls do not move individually but rather move in groups or lumps, reducing the shear stress between the grinding balls and preventing grinding from progressing. In addition, by using grinding balls with a mass of 11.00 mg / piece or less, it is possible to prevent the aluminum powder from being subjected to excessive impact force, and to prevent the occurrence of warping, distortion, cracks, and the like. Instead of the ball mill, a media stirring mill can be used in the same manner as above. As the media stirring mill, for example, a screw type (tower type), stirring tank type, flow pipe type, annular (ring) type, etc. can be used.
[0028] <Raw material aluminum powder> The atomized aluminum powder (raw metallic aluminum powder) used as the raw material is preferably one that contains few impurities other than aluminum. The purity of the atomized aluminum powder is preferably 99.5% or more, more preferably 99.7% or more, and even more preferably 99.8% or more.
[0029] The average particle size of the atomized aluminum powder used as the raw material is preferably 1.0 to 6.0 μm, and more preferably 1.5 to 5.0 μm. When the atomized aluminum powder has an average particle size of 1.0 μm or more, the energy applied to the particles during grinding is not excessive, warping and distortion of the particles can be prevented, and good particle shape can be maintained, which is preferable. The shape of the atomized aluminum powder used as the raw material is preferably spherical or teardrop-shaped. By using these, the shape of the aluminum pigment tends to be less likely to be distorted during grinding. On the other hand, acicular powder and amorphous powder are not preferred because the shape of the aluminum pigment is easily distorted during grinding.
[0030] <Grinding solvent> When the aluminum pigment of the present embodiment is produced by a grinding device equipped with a ball mill or the like, it is preferable to use a grinding solvent. The type of the grinding solvent is not limited to the following, but examples thereof include conventionally used hydrocarbon solvents such as mineral spirits and solvent naphtha, and low viscosity solvents such as alcohols, ethers, ketones, and esters. As for the grinding conditions of the atomized aluminum powder, the volume of the grinding solvent relative to the mass of aluminum in the atomized aluminum powder is preferably 1.5 to 16.0 times, and more preferably 2.0 to 12.0 times. By setting the volume of the grinding solvent to 1.5 times or more relative to the mass of aluminum in the atomized aluminum powder, warping, distortion, cracks, etc., which are caused by grinding the atomized aluminum powder for a long period of time can be prevented, which is preferable. In addition, by having the volume of the grinding solvent be 16.0 times or less relative to the mass of aluminum in the atomized aluminum powder, uniformity within the mill during grinding is improved, the atomized aluminum powder comes into efficient contact with the grinding media, and grinding tends to proceed smoothly.
[0031] The volume of the grinding balls relative to the volume of the grinding solvent (volume of grinding balls / volume of grinding solvent) is preferably 0.5 to 3.5 times, and more preferably 0.8 to 2.5 times. By making the volume of the grinding balls 0.5 times or more the volume of the grinding solvent, the uniformity of the grinding balls in the mill during grinding is improved, and grinding tends to proceed smoothly. In addition, by making the volume of the grinding balls 3.5 times or less relative to the volume of the grinding solvent, the ratio of the grinding balls in the mill is in a suitable range, and the stacking of the balls is not too high, which prevents problems of shape deterioration such as warping, distortion, and cracking of the particles due to grinding stress, and is preferable in that it prevents a decrease in brightness and increased scattered light.
[0032] <Grinding aid> When the aluminum pigment of this embodiment is produced using a grinding device equipped with a ball mill, it is preferable to use a grinding aid in addition to the above-mentioned grinding solvent. The grinding aid may be any one that exhibits the characteristics of a non-leafing pigment, and examples thereof include, but are not limited to, higher unsaturated fatty acids such as oleic acid, higher aliphatic amines such as stearin amine, higher aliphatic alcohols such as stearyl alcohol and oleyl alcohol, higher fatty acid amides such as stearic acid amide and oleic acid amide, and higher fatty acid metal salts such as aluminum stearate and aluminum oleate. The grinding aid is preferably used in an amount of 0.2 to 30% by mass based on the mass of the atomized aluminum powder.
[0033] <Ball mill> The ball mill used for grinding the atomized aluminum powder preferably has a diameter of 0.6 mm to 2.4 mm, and more preferably has a diameter of 0.8 mm to 2.0 mm. By using a ball mill with a diameter of 0.6 mm or more, the stacking of the grinding balls does not become too low, the pressure applied to the aluminum particles during the grinding process falls within an appropriate range, and grinding tends to proceed smoothly. In addition, by using a ball mill with a diameter of 2.4 mm or less, the stacking of the grinding balls does not become too high, which prevents problems of shape deterioration such as warping, distortion, and cracking of the particles due to the weight of the balls, and is preferable because it prevents a decrease in brightness and increased scattered light.
[0034] As described above, the rotation speed of the ball mill during grinding of the atomized aluminum powder is preferably 33% to 78% of the critical rotation speed (Nc), and more preferably 36% to 57%. A ratio of the rotation speed to the critical rotation number of 33% or more is preferable because it maintains uniformity of the aluminum slurry and ball movement in the ball mill. In addition, by keeping the ratio of rotation speed / critical rotation number at 78% or less, the behavior of the grinding balls being scraped up or falling under their own weight is prevented, and the impact force applied to the aluminum particles from the grinding balls does not become too high, thereby preventing problems of shape deterioration such as warping, distortion, and cracking of the particles, which is preferable.
[0035] The aluminum pigment of the present embodiment can also be produced by a vacuum deposition method other than the above-mentioned production method having a step of grinding atomized aluminum powder.
[0036] <Classification process> Furthermore, after the aluminum pigment of this embodiment has been subjected to the above-mentioned grinding step, the ground slurry can be classified to remove particles with a large aspect ratio and small particles. One method for this is, for example, a liquid cyclone classification method. Classification can be performed by subjecting the ground slurry to a two-liquid separation type liquid cyclone classifier and / or a three-liquid separation type liquid cyclone classifier. As for classification conditions, the classification operation can be optimized by appropriately adjusting conditions such as nozzle diameter, flow rate (L / min), and operating pressure (MPa) according to the purpose.
[0037] Furthermore, the aluminum pigment of this embodiment may have any aspect ratio average value, standard deviation, and particle number ratio with a particle diameter of 0.2 to 2.0 μm within the above-mentioned numerical ranges, and it is also possible to mix and adjust multiple aluminum pigments with different ranges according to the final desired design.
[0038] [Paint composition] The coating composition of the present embodiment contains the aluminum pigment of the present embodiment described above. The coating composition of the present embodiment can contain, in addition to the aluminum pigment, mica, color pigments, and the like. Furthermore, the coating composition of this embodiment may contain various resins and various additives such as antioxidants, light stabilizers, polymerization inhibitors, and surfactants. The coating composition of the present embodiment can be produced by mixing the aluminum pigment with various other materials as required. The coating composition of the present embodiment can be used as a metallic coating.
[0039] [Ink composition] The ink composition of this embodiment contains the aluminum pigment of this embodiment described above. The ink composition of the present embodiment may contain, in addition to the aluminum pigment described above, a predetermined color pigment, a solvent, and the like. The ink composition of the present embodiment may further contain various resins and various additives such as antioxidants, light stabilizers, polymerization inhibitors, and surfactants. The ink composition of the present embodiment can be produced by mixing the aluminum pigment with various other materials as necessary, and can be used as a metallic ink.
[0040] [Other uses] In addition, the aluminum pigment of the present embodiment can be kneaded with a resin or the like and used as a water-resistant binder or filler. EXAMPLES
[0041] The present embodiment will be described in more detail below with reference to examples and comparative examples. The present embodiment is not limited in any way by the following examples. The methods for measuring various physical properties used in the examples and comparative examples are as follows.
[0042] [(I) Thickness and aspect ratio of metallic aluminum particles] ((1) Preparation of painted boards) Using the aluminum pigments obtained in the Examples and Comparative Examples described below, metallic paints were prepared according to the following compositions. Aluminum pigment: 1g Thinner: 50g (Musashi Paint Co., Ltd., product name "Plaace Thinner No. 2726") Acrylic resin: 33g (Musashi Paint Co., Ltd., product name "Plaace No. 7160") The above paint was applied to an ABS resin plate using an air spray device so that the dry film thickness was 20 μm, and the plate was dried in an oven at 60° C. for 30 minutes to obtain a coated plate for evaluation.
[0043] ((2) Cross-section preparation of coating film) Using the coated plate for evaluation produced as described above, a cross section of the coating film was prepared in the following manner: Using scissors, the coated plate for evaluation was cut into pieces measuring 1 cm square. The cut 1 cm square coating plate for evaluation was repeatedly cut along the cross section of the coating using a large rotary microtome (manufactured by Yamato Koki Kogyo Co., Ltd. / RV-240) to remove the microscopic aluminum-acrylic resin protruding from the cross section. The cross-section of the coating film obtained as described above was subjected to ion milling using an ion milling device (JEOL Ltd. / IB-09010CP) with the position of a shielding plate set so that the ion beam could be irradiated up to a portion 20 μm away from the cross-section of the coating film, to prepare a cross-section of the coating film for obtaining an FE-SEM image as described below.
[0044] ((3) Acquisition of particle cross-section (FE-SEM image) The coating cross-section (coated plate) obtained in the above ((2) Preparation of coating cross-section) was attached parallel to the SEM sample stage, and a field emission type FE-SEM (Hitachi / S-4700) was used to obtain an FE-SEM image of the coating cross-section. The conditions for FE-SEM observation and acquisition were as follows: the accelerating voltage was set to 10 kV, and the image magnification was set to 3,000 to 10,000. The magnification was changed appropriately depending on the size of the particles, and images were taken at a magnification where the particles were within the field of view. In addition, before acquiring (capturing) the FE-SEM image, an electronic axis alignment process was performed to prevent distortion of the boundary between the aluminum particles and the acrylic resin in the FE-SEM image, and the brightness and contrast were appropriately set to allow clear and distinct identification of the particles. The image was taken at a high resolution of 2560 x 1920 pixels. Only when a clear image was obtained without any cracks or damage caused by the ion milling cross-section processing of the sample was it adopted as a measurement image, and the image was left unprocessed without any processing.
[0045] ((4) Analysis (measuring particle size in cross section: particle thickness, aspect ratio) The FE-SEM images obtained by the procedure for obtaining particle cross sections (FE-SEM images) described above ((I)-(3)) were used to measure the length and area of the aluminum particle cross sections using image analysis software Image Pro Plus version 7.0 (manufactured by Media Cybernetics), and the thickness and aspect ratio were calculated. The FE-SEM images for measuring the length and area of the cross section of the aluminum particle were read into image analysis software, and the scale length and unit were set by performing spatial calibration. Next, the particle outlines were accurately extracted, and measurements of two items, area and size (length), were obtained. The particles were extracted using a free curve AOI tool and converted into objects. The particle images were then enlarged as needed to correct the objects and accurately extract the particle outlines. Particles that were outside the image or were unclear were excluded from the measurement. The measured particle size (length) was taken as the "particle cross-sectional length," and the calculated ratio of the area to the size (length) (area / size (length)) was taken as the "particle cross-sectional thickness." In addition, the calculated ratio of the particle cross-sectional length to the particle cross-sectional thickness (particle cross-sectional length / particle cross-sectional thickness) was taken as the "particle aspect ratio." Particle cross-sectional length = size (length) measurement Particle cross-sectional thickness = Area / Size (length) Aspect ratio = particle cross-sectional length / particle cross-sectional thickness This procedure was repeated to determine the aspect ratios of 100 or more particles.
[0046] [(II) Evaluation of average thickness, average aspect ratio, standard deviation of aspect ratio, and number ratio of metallic aluminum particles] The overall average particle cross-sectional thickness (area / size (length)) (average thickness t) of 100 or more particles obtained by the above analysis ((I)-(4)), the average aspect ratio (particle cross-sectional length / particle cross-sectional thickness) (average aspect ratio), the standard deviation of the aspect ratios, and the proportion of particles with aspect ratios in the range of 20 or less and 110 or more relative to the total number of particles were determined.
[0047] (III) Analysis (measuring particle size in cross section: particle planarity) ((1) Evaluation of particle planarity) The planarity (shortest length / particle cross-sectional length) of the aluminum particles was measured using the image analysis software Win Roof version 5.5 (MITANI CORPORATION) for the FE-SEM images obtained by the procedure for obtaining particle cross-sections (FE-SEM images) described above ((I)-(3)). FIG. 3 shows an example image of the measurement of particle planarity (shortest length / particle cross-sectional length). The straight line tool and curved line tool of the image analysis software Win Roof version 5.5 were selected, and the measurement value of a straight line connecting both ends of the cross section of the aluminum particle was taken as the shortest length, and the measurement value of a line connecting both ends along the cross section of the aluminum particle was taken as the particle cross-sectional length, and the value of (shortest length / particle cross-sectional length) was taken as the planarity of the aluminum particle. This procedure was repeated to determine the planarity values of 100 particles. Moreover, the aluminum particles selected for determining the flatness value were those within ±50% of the average particle diameter: d50 described below. The closer the flatness value of a particle is to 1.00, the smaller the degree of warping, distortion, etc. of the particle is.
[0048] ((2) Average particle diameter d50) The average particle size (d50) of the aluminum pigment was measured using a laser diffraction / scattering type particle size distribution analyzer (LA-300 / HORIBA, Ltd.). Mineral spirits was used as the measurement solvent. The measurements were carried out in accordance with the equipment's instruction manual, but it should be noted that the aluminum pigment sample was ultrasonically dispersed for 2 minutes as a pretreatment, then placed in the dispersion tank and the measurements were started after confirming that the appropriate concentration had been achieved. After the measurement was completed, d50 was automatically displayed.
[0049] ((3) Proportion of planar particles) From the planarity (shortest length / particle cross-sectional length) values of 100 particles obtained above, the threshold value of particle planarity was set to 0.95, and the percentage of aluminum particles falling within the range of 0.95 to 1.00 was obtained. In the aluminum pigment of this embodiment, the proportion of planar particles having a particle planarity in the range of 0.95 to 1.00 is 60% or more.
[0050] [(IV) Proportion of particles with diameters of 0.2 to 2.0 μm] ((1) Preparation of painted boards) Using the aluminum pigments obtained in the Examples and Comparative Examples described below, metallic paints were prepared according to the following compositions. Aluminum pigment: 0.25g Thinner: 12.75g (Product name: "Acrylic 2000GL Thinner" manufactured by Kansai Paint Co., Ltd.) Acrylic resin: 97.00g (Product name: "Aclick 2000 Clear" manufactured by Kansai Paint Co., Ltd.) Next, the prepared paint was shaken for 10 minutes using a paint shaker, and the paint was applied onto a hiding rate test paper (manufactured by Taiyu Kizai Co., Ltd., product name "Hiding rate measurement paper H-100 JIS compliant product") using a bar coater No. 6, and dried at room temperature to obtain a coated plate for evaluation. ((2) Obtaining images of the surface of aluminum pigment particles) The coating film (coated plate) obtained in the above ((1) Preparation of Coated Plate) was observed using a microscope (Hirox / KH-3000) to obtain an observation image of the particle surface of the coating film. The image magnification was set to 2100x, and 10 fields of view were photographed per sample. ((3) Analysis (particle counting, size measurement)) The image obtained by the procedure for obtaining an observation image of the aluminum pigment particle surface described above ((IV)-(2)) was used to measure the diameters of all aluminum particles that could be clearly and uninterruptedly confirmed in the image using image analysis software Image Pro Plus version 7.0 (Media Cybernetics), and the proportion of particles with diameters of 0.2 to 2.0 μm to the total was calculated, assuming the total number of particles to be 100 or more. At this time, particles that overlapped with each other and had an unclear shape, and particles whose outlines were unclear and difficult to judge, were excluded from the measurement. The particle extraction method was to accurately extract the particle contours by manual measurement, and the measurement item selected was diameter (average), which was used as the particle diameter value. ((4) Evaluation of the number of particles with diameters of 0.2 to 2.0 μm) The above analysis ((IV)-(3)) was carried out on 10 visual fields per sample, and the proportion of particles with an average diameter of 0.2 to 2.0 μm was determined relative to the total number of aluminum particles (100 or more) in all 10 visual fields. Moreover, when the number of measured particles was less than 100, the image was acquired again to increase the number of fields of view, and the number of measured particles was set to 100 or more.
[0051] (V) Arithmetic mean height of particle surface roughness: Sa) The arithmetic mean height Sa of the surface roughness of the metallic aluminum particles in the aluminum pigment was measured by the following method. ((1) Pretreatment) The aluminum pigments obtained in the Examples and Comparative Examples described below were mixed with mineral spirits and solvent naphtha, and therefore were subjected to a washing treatment. 100 mg of Al paste (aluminum pigment) was placed in a screw tube, and 5 mL of toluene was added. The mixture was dispersed by shaking with a hand shake for several tens of seconds, and then centrifuged. The supernatant was removed, and 5 mL of toluene was added again, followed by dispersion and centrifugation in the same manner. A small amount (approximately a few mg) of the precipitated Al paste was collected, dispersed in 5 mL of toluene, and dropped onto a 1 cm square silicon wafer and air-dried. ((2) Acquiring images for measurement) The arithmetic mean height Sa of the surface roughness of the particles was measured under the following conditions. Particles that could secure a 4 μm square field of view were selected, and images for measurement were obtained under the following conditions. Equipment: Hitachi High-Tech AFM5100N Measurement mode: DFM Probe: PRC-DF40P Measurement field of view: 4μm square / 512pixel ((3) Analysis and calculation of Sa) The analysis was performed using the analysis software provided with the device. After performing a first-order slope correction, Sa was calculated using the roughness analysis function. Software: AFM5000II Post-measurement correction: First-order tilt correction Roughness measurement: Sa (automatic calculation)
[0052] (VI) Evaluation of denseness, brightness, luminosity, and glossiness ((1) Preparation of paints and painted panels) Using the aluminum pigments obtained in the Examples and Comparative Examples described below, metallic paints were prepared according to the following compositions. Aluminum pigment: 1.25g Mixed thinner: 8.75g (Solvent mixing ratio: methyl ethyl ketone: 40% by mass, ethyl acetate: 40% by mass, Isopropyl alcohol: 20% by mass Polyurethane resin: 4.00g (Manufactured by Sanyo Chemical Industries, Ltd., product name "Sanprene IB Series 1700D") Next, the prepared coating material was dispersed with a magnetic stirrer at 500 rpm for 20 minutes, and then coated onto a PET film using a No. 6 bar coater, followed by drying at room temperature to obtain a coated plate for evaluation.
[0053] ((2) Measurement of density, brightness, luminosity, and glossiness) (i) Sense of precision As an index showing denseness, BYK-mac (manufactured by BYK Gardner) was used to evaluate the graininess. To evaluate the graininess, diffuse light (-15 degrees, 45 degrees, 75 degrees) was detected by a camera detector (0 degree), and the uniformity of the light and dark areas was displayed as a numerical value. The uniformity of the light and dark areas was measured by reading the graininess value, with a smaller value indicating a more dense appearance. (ii) Luminance, brightness The luminance and brightness were evaluated using a color meter VC-2 (manufactured by Suga Test Instruments Co., Ltd.). The luminance was measured at an incident angle of 45 degrees and a receiving angle of 5 degrees (L5), which is close to regular reflected light and excludes the light in the specular reflection area reflected by the coating surface.The lightness was then measured at a receiving angle of 50 degrees shifted to 55 degrees (L55). Brightness is a parameter proportional to the intensity of specularly reflected light from an aluminum pigment, and it was determined that the greater the measured value, the higher the specularly reflected light intensity and the better the product. Brightness can be measured by capturing the changes in brightness that appear differently depending on the angle; the higher the L value for each angle, the higher the intensity of the light reflected at that angle, and the higher the measured value, the higher the brightness. (iii) Glossiness The gloss level was evaluated using a UGV-5D (manufactured by Suga Test Instruments Co., Ltd.) When the reflectance was measured when the incident angle and receiving angle were both 60 degrees according to the 60-degree specular gloss level, it was determined that the greater the 60-degree specular reflectance, the higher the gloss level of the coating film and the more excellent its optical properties.
[0054] (VII) Evaluation of Dispersibility ((1) Preparation of evaluation samples) Using the aluminum pigments obtained in the Examples and Comparative Examples described below, evaluation samples were prepared according to the following compositions. (i) Weigh out 10 g of an aluminum pigment sample into a disposable cup (500 ml). (ii) Add 100 ml of xylene to the above (i) to prepare the test sample.
[0055] ((2) Dispersibility test evaluation) The evaluation samples prepared in (1) above were tested and evaluated according to the following methods. (i) The test sample is dispersed by stirring at 500 rpm for 1 minute using a Three-One motor. (ii) This dispersion is transferred to another disposable cup, and the presence or absence of undispersed sample at the bottom of the disposable cup is confirmed. (iii) If undispersed sample is present, return the transferred dispersion liquid and repeat the measurement procedures from (i) to (ii) until no undispersed sample remains. (iv) The time required for the undispersed sample to disappear was judged as follows, and the shorter the time required, the better the dispersibility was judged to be.
[0056] Example A1 A mixture consisting of 9.5 kg of raw metal atomized aluminum powder (average particle size: 2.1 μm), 45.8 kg of mineral spirits, and 570 g of oleic acid was loaded into a ball mill having an inner diameter of 2 m and a length of 30 cm, and ground using 309 kg of zirconia balls having a diameter of 0.8 mm. The zirconia balls used were those containing 94 mass % or more of ZrO2 as the main component and having a circularity rate of 95% or more. The ball mill rotation speed was set to 13 rpm (ratio of rotation speed / critical rotation speed was 43%), and grinding was carried out for 150 hours. After grinding, the slurry in the mill was washed out with mineral spirits and classified using a liquid cyclone classifier. First, the top nozzle diameter was set to φ5 mm, the bottom nozzle diameter was set to φ2 mm, and the pressure was set to 0.4 MPa, and the slurry was passed through a two-liquid separation type liquid cyclone classifier to obtain a slurry classified on the top side. Next, the top nozzle diameter was set to φ3 mm, the middle nozzle diameter was set to φ6 mm, the bottom nozzle diameter was set to φ1.5 mm, and the pressure was set to 0.6 MPa, and the slurry was further passed through a three-liquid separation type liquid cyclone classifier to obtain a slurry classified on the bottom side. The classified slurry was filtered and concentrated to obtain a cake with a heating residue of 76 mass%. The obtained cake was transferred into a vertical mixer, a predetermined amount of solvent naphtha was added, and the mixture was mixed for 20 minutes to obtain an aluminum pigment having a heating residue of 66% by mass. The aluminum pigment thus obtained was evaluated for the average thickness, average aspect ratio, standard deviation of aspect ratio, number of particles having an aspect ratio of 20 or less, number of particles having an aspect ratio of 110 or more, number of planar particles, arithmetic mean height Sa of particle surface roughness, and number of particles having a particle diameter of 0.2 to 2.0 μm by the above (I) to (V), and for the denseness, brightness, lightness, dispersibility, and glossiness by the above (VI) and (VII). The evaluation results are shown in Table A1.
[0057] Example A2 Atomized aluminum powder (average particle size: 2.5 μm) was used as raw material and ground using zirconia balls with a diameter of 1.3 mm. The ball mill rotation speed was set to 17 rpm (ratio of rotation speed / critical rotation speed was 57%), and grinding was carried out for 50 hours. The other conditions were the same as in Example A1, and an aluminum pigment having a heating residue of 70% by mass was obtained. The obtained aluminum pigment was evaluated for denseness, brightness, lightness, dispersibility, and glossiness according to the above (VI) and (VII). The evaluation results are shown in Table A1.
[0058] Example A3 The aluminum pigments obtained in the following (1) and (2) were mixed in a 1:1 ratio to obtain an aluminum pigment. (1) A mixture of atomized aluminum powder (average particle size: 1.9 μm) was filled with 53.4 kg of mineral spirits and 950 g of oleic acid, and ground using 309 kg of zirconia balls with a diameter of 1.7 mm. The ball mill rotation speed was set to 13 rpm (ratio of rotation speed / critical rotation speed was 43%), and grinding was carried out for 80 hours. The other conditions were the same as in Example A1, and an aluminum pigment having a heating residue of 68% by mass was obtained. (2) Also, using raw material metal atomized aluminum powder (average particle size: 2.8 μm), the same operation as in (1) above was carried out under other conditions to obtain an aluminum pigment having a heating residue of 70 mass %. (3) The obtained aluminum pigment was evaluated for denseness, brightness, lightness, dispersibility, and glossiness according to the above (VI) and (VII). The evaluation results are shown in Table A1.
[0059] Example A4 The rotation speed of the ball mill was set to 17 rpm (the ratio of rotation speed / critical rotation speed was 57%). Other conditions were the same as in Example A1. The obtained aluminum pigment was evaluated for denseness, brightness, lightness, dispersibility, and glossiness according to the above (VI) and (VII). The evaluation results are shown in Table A1.
[0060] [Comparative Example A1] Grinding was carried out using the same composition and under the same grinding conditions as in Example A1. After grinding was completed, the slurry in the mill was washed out with mineral spirits, passed through a 400 mesh vibrating sieve to remove coarse particles, filtered and concentrated to obtain a cake with a heating residue of 74% by mass (no classification step was carried out). The obtained cake was transferred into a vertical mixer, a predetermined amount of solvent naphtha was added, and the mixture was mixed for 20 minutes to obtain an aluminum pigment having a heating residue of 64% by mass. The obtained aluminum pigment was evaluated for denseness, brightness, lightness, dispersibility, and glossiness according to the above (VI) and (VII). The evaluation results are shown in Table A1.
[0061] [Comparative example A2] The same compound as in Example A1 was filled in the above, and the ball mill speed was changed to 25 rpm (ratio of rotation speed / critical rotation speed: 83%) to carry out grinding. After grinding was completed, the slurry in the mill was washed out with mineral spirits, passed through a 400 mesh vibrating sieve to remove coarse particles, filtered and concentrated to obtain a cake with a heating residue of 72% by mass (no classification step was carried out). The obtained cake was transferred into a vertical mixer, a predetermined amount of solvent naphtha was added, and the mixture was mixed for 20 minutes to obtain an aluminum pigment having a heating residue of 62% by mass. The obtained aluminum pigment was evaluated for denseness, brightness, lightness, dispersibility, and glossiness according to the above (VI) and (VII). The evaluation results are shown in Table A1.
[0062] [Comparative example A3] Grinding was carried out using raw material metal atomized aluminum powder (average particle size: 6.5 μm). The other ingredients and grinding conditions were the same as those in [Example A1]. After grinding was completed, the slurry in the mill was washed out with mineral spirits, passed through a 400 mesh vibrating sieve to remove coarse particles, filtered and concentrated to obtain a cake with a heating residue of 76% by mass (no classification step was carried out). The obtained cake was transferred into a vertical mixer, a predetermined amount of solvent naphtha was added, and the mixture was mixed for 20 minutes to obtain an aluminum pigment having a heating residue of 66% by mass. The obtained aluminum pigment was evaluated for denseness, brightness, lightness, dispersibility, and glossiness according to the above (VI) and (VII). The evaluation results are shown in Table A1.
[0063] [Comparative example A4] The raw material metal atomized aluminum powder (average particle size: 2.2 μm) was used for grinding. The ball mill rotation speed was set to 11 rpm (ratio of rotation speed / critical rotation speed was 37%), and grinding was carried out for 110 hours. The other ingredients and grinding conditions were the same as in Example A1. After grinding was completed, the slurry in the mill was washed out with mineral spirits, passed through a 400 mesh vibrating sieve to remove coarse particles, filtered and concentrated to obtain a cake with a heating residue of 78% by mass (no classification step was performed). The obtained cake was transferred into a vertical mixer, a predetermined amount of solvent naphtha was added, and the mixture was mixed for 20 minutes to obtain an aluminum pigment having a heating residue of 68% by mass. The obtained aluminum pigment was evaluated for denseness, brightness, lightness, dispersibility, and glossiness according to the above (VI) and (VII). The evaluation results are shown in Table A1.
[0064] [Table A1]
[0065] From Table A1, it is clear that the aluminum pigment of the present invention is dense, has extremely high brightness and luminosity, and also has good dispersibility and workability.
[0066] [Example B1] A mixture consisting of 9.5 kg of raw metal atomized aluminum powder (average particle size: 2.4 μm), 45.8 kg of mineral spirits, and 570 g of oleic acid was loaded into a ball mill having an inner diameter of 2 m and a length of 30 cm, and ground using 309 kg of zirconia balls having a diameter of 0.8 mm. The zirconia balls used were those containing 94 mass % or more of ZrO2 as the main component and having a circularity rate of 95% or more. The ball mill rotation speed was set to 13 rpm (ratio of rotation speed / critical rotation speed was 43%), and the first stage of grinding was carried out for 100 hours. After the first stage of grinding, 9.2 kg of mineral spirits and 114 g of oleic acid were added to the ball mill, and the ball mill rotation speed was set to 23 rpm (ratio of rotation speed / critical rotation speed: 77%), and the second stage of grinding was carried out for 6 hours. After grinding, the slurry in the mill was washed out with mineral spirits and classified using a liquid cyclone classifier. The top nozzle was set to a diameter of φ5 mm, the bottom nozzle to a diameter of φ2 mm, and the pressure was set to 0.4 MPa. The slurry was passed through a two-liquid separation type liquid cyclone classifier, and the classified slurry was obtained on the top side. The classified slurry was filtered and concentrated to obtain a cake with a heating residue of 76% by mass. The obtained cake was transferred into a vertical mixer, a predetermined amount of solvent naphtha was added, and the mixture was mixed for 20 minutes to obtain an aluminum pigment having a heating residue of 66% by mass. The aluminum pigment thus obtained was evaluated for the average thickness, average aspect ratio, standard deviation of aspect ratio, percentage of particles having an aspect ratio of 20 or less, percentage of particles having an aspect ratio of 110 or more, percentage of planar particles, arithmetic mean height Sa of particle surface roughness, and percentage of particles having a particle diameter of 0.2 to 2.0 μm according to (I) to (V) above, and for the denseness, brightness, lightness, dispersibility, and gloss according to (VI) and (VII) above. The evaluation results are shown in Table B1.
[0067] Example B2 Atomized aluminum powder (average particle size: 2.5 μm) was used as raw material and ground using zirconia balls with a diameter of 1.3 mm. The grinding conditions for the first stage were a ball mill rotation speed of 10 rpm (ratio of rotation speed / critical rotation speed: 33%), and grinding was performed for 60 hours. The second stage grinding conditions were a ball mill rotation speed of 23 rpm (ratio of rotation speed / critical rotation speed: 77%), and grinding was performed for 10 hours. Other conditions were the same as in [Example B1], and an aluminum pigment with a heating residue of 68% by mass was obtained. The obtained aluminum pigment was evaluated for denseness, brightness, lightness, dispersibility, and glossiness according to the above (VI) and (VII). The evaluation results are shown in Table B1.
[0068] [Example B3] Atomized aluminum powder (average particle size: 2.3 μm) was used as raw material and ground using zirconia balls with a diameter of 1.0 mm. The grinding conditions for the first stage were a ball mill rotation speed of 11 rpm (ratio of rotation speed / critical rotation speed: 37%), and grinding was performed for 70 hours. The second grinding condition was a ball mill rotation speed of 23 rpm (ratio of rotation speed / critical rotation speed: 77%), and grinding was performed for 7 hours. The other conditions were the same as in [Example B1], and an aluminum pigment with a heating residue of 66% by mass was obtained. The obtained aluminum pigment was evaluated for denseness, brightness, lightness, dispersibility, and glossiness according to the above (VI) and (VII). The evaluation results are shown in Table B1.
[0069] [Example B4] Atomized aluminum powder (average particle size: 3.2 μm) was used as raw material and ground using zirconia balls with a diameter of 1.7 mm. The grinding conditions for the first stage were a ball mill rotation speed of 10 rpm (ratio of rotation speed / critical rotation speed: 33%), and grinding was performed for 45 hours. The second grinding condition was a ball mill rotation speed of 23 rpm (ratio of rotation speed / critical rotation speed: 77%), and grinding was performed for 12 hours. The other conditions were the same as in [Example B1], and an aluminum pigment with a heating residue of 70% by mass was obtained. The obtained aluminum pigment was evaluated for denseness, brightness, lightness, dispersibility, and glossiness according to the above (VI) and (VII). The evaluation results are shown in Table B1.
[0070] [Example B5] Atomized aluminum powder (average particle size: 2.8 μm) was used as raw material and ground using zirconia balls with a diameter of 1.3 mm. The grinding conditions for the first stage were a ball mill rotation speed of 12 rpm (ratio of rotation speed / critical rotation speed: 40%), and grinding was performed for 50 hours. The other conditions were the same as in Example B1, and an aluminum pigment having a heating residue of 69% by mass was obtained. The obtained aluminum pigment was evaluated for denseness, brightness, lightness, dispersibility, and glossiness according to the above (VI) and (VII). The evaluation results are shown in Table B1.
[0071] [Comparative Example B1] A mixture similar to that used in Example B1 was used, and the first stage of grinding was carried out under conditions of a ball mill rotation speed of 6 rpm (ratio of rotation speed / critical rotation speed: 20%) for 100 hours. The grinding conditions for the second stage were the ball mill rotation speed of 6 rpm (ratio of rotation speed / critical rotation speed: 20%), which was the same as in the first stage, and grinding was carried out for 8 hours. The other conditions were the same as in Example B1, and an aluminum pigment having a heating residue of 70% by mass was obtained. The obtained aluminum pigment was evaluated for denseness, brightness, lightness, dispersibility, and glossiness according to the above (VI) and (VII). The evaluation results are shown in Table B1.
[0072] [Comparative example B2] The same raw metal atomized aluminum powder as in Example B1 was used, and a mixture consisting of 42 kg of mineral spirits and 950 g of stearylamine was charged and ground using 408 kg of steel balls having a diameter of 0.8 mm. The grinding conditions for the first stage were a ball mill rotation speed of 13 rpm (ratio of rotation speed / critical rotation speed: 43%). After the first stage of grinding, 8.4 kg of mineral spirits and 190 g of stearylamine were added to the ball mill, and the ball mill rotation speed was set to 23 rpm (ratio of rotation speed / critical rotation speed: 77%), and the second stage of grinding was carried out for 8 hours. The other conditions were the same as in Example B1, and an aluminum pigment having a heating residue of 64% by mass was obtained. The obtained aluminum pigment was evaluated for denseness, brightness, lightness, dispersibility, and glossiness according to the above (VI) and (VII). The evaluation results are shown in Table B1.
[0073] [Comparative Example B3] The first stage of grinding was carried out using raw material metal atomized aluminum powder (average particle size: 6.2 μm). The second grinding condition was a ball mill rotation speed of 6 rpm (ratio of rotation speed / critical rotation speed: 20%), and grinding was performed for 8 hours. The other ingredients and grinding conditions were the same as in Example B1. After grinding was completed, the slurry in the mill was washed out with mineral spirits, passed through a 400 mesh vibrating sieve to remove coarse particles, filtered and concentrated to obtain a cake with a heating residue of 78% by mass (no classification step was performed). The obtained cake was transferred into a vertical mixer, a predetermined amount of solvent naphtha was added, and the mixture was mixed for 20 minutes to obtain an aluminum pigment having a heating residue of 68% by mass. The obtained aluminum pigment was evaluated for denseness, brightness, lightness, dispersibility, and glossiness according to the above (VI) and (VII). The evaluation results are shown in Table B1.
[0074] [Comparative example B4] The aluminum pigment produced by the metal deposition method (without grinding or classification) of Metalure L 55700 manufactured by Eckart was evaluated for denseness, brightness, luminosity, dispersibility, and glossiness according to the above (VI) and (VII). The evaluation results are shown in Table B1.
[0075] [Table B1]
[0076] The results shown in Table B1 reveal that the aluminum pigment of the present invention is dense, has extremely high brightness, luminosity and gloss, and also has good dispersibility and workability. [Industrial Applicability]
[0077] INDUSTRIAL APPLICABILITY The aluminum pigment of the present invention has industrial applicability in the fields of high-end metallic paints for automobile bodies and automobile interior parts, metallic paints for automobile repairs, metallic paints for home appliances, metallic paints for optical devices such as mobile phones, smartphones, PCs, tablets, cameras, and televisions, PCM, industrial metallic paints, high-end metallic printing inks such as gravure printing, offset printing, and screen printing, and as a material for kneading into high-end metallic resins.
Claims
1. An aluminum pigment, wherein the average thickness of metallic aluminum particles is 0.02 to 0.20 μm, the average aspect ratio (particle cross-sectional length / particle cross-sectional thickness) is 40 to 90, and the standard deviation of the aspect ratio is 15 to 47.1, and the proportion of particles having an aspect ratio of 110 or more is 30% or less relative to the total number of particles.
2. 2. The aluminum pigment according to claim 1, wherein the proportion of particles having an aspect ratio of 20 or less by number is 30% or less relative to the total number of particles.
3. 3. The aluminum pigment according to claim 1, wherein the particles have an arithmetic mean height Sa of surface roughness of 2 to 15 nm.
4. 4. The aluminum pigment according to claim 1, wherein the particles have an average thickness of 0.03 to 0.15 μm.
5. 5. The aluminum pigment according to claim 1, wherein the particles have an average aspect ratio of 40 to 90.
6. 6. The aluminum pigment according to claim 1, comprising metallic aluminum particles in which the number ratio of particles having a particle diameter of 0.2 to 2.0 μm is 15 to 70% of the total number of metallic aluminum particles.
7. 7. The aluminum pigment according to claim 1, wherein the particles are planar particles having a planarity (shortest length / particle cross-sectional length) of 0.95 to 1.00 in a number ratio of 60% or more.
8. 8. A method for producing the aluminum pigment according to claim 1, comprising the steps of grinding a raw material aluminum metal powder by a grinding device and classifying a slurry obtained after grinding.
9. The method for producing an aluminum pigment according to claim 8, wherein the grinding step is carried out in two stages.
10. A coating composition comprising the aluminum pigment according to any one of claims 1 to 7.
11. An ink composition comprising the aluminum pigment according to any one of claims 1 to 7.
Citation Information
Patent Citations
METHOD FOR MANUFACTURING METAL FLAKES
JP2002528639A
Aluminum flake pigment, coating composition containing the same, ink composition and coating film thereof
JP2003082258A
Pigment dispersion, ink composition, inkjet recording method and recorded material
JP2008174712A
Inkjet printing ink and method containing thin aluminum-effect pigment
JP2010533747A
Thin aluminum pigment having narrow thickness distribution, its manufacturing method and its use
JP2014159583A